Chagas disease vector control in a hyperendemic setting: the first 11 years of intervention in Cochabamba, Bolivia. - Natalisisy Espinoza; Rafael Borrás; Fernando Abad-Franch (Public Library of Science (PLoS), 2014)
BACKGROUND: Chagas disease has historically been hyperendemic in the Bolivian Department of Cochabamba. In the early 2000s, an extensive vector control program was implemented; 1.34 million dwelling inspections were conducted to ascertain infestation (2000-2001/2003-2011), with blanket insecticide spraying in 2003-2005 and subsequent survey-spraying cycles targeting residual infestation foci. Here, we assess the effects of this program on dwelling infestation rates (DIRs). METHODOLOGY/PRINCIPAL FINDINGS: Program records were used to calculate annual, municipality-level aggregate DIRs (39 municipalities); very high values in 2000-2001 (median: 0.77-0.69) dropped to ∼0.03 from 2004 on. A linear mixed model (with municipality as a random factor) suggested that infestation odds decreased, on average, by ∼28% (95% confidence interval [CI95] 6-44%) with each 10-fold increase in control effort. A second, better-fitting mixed model including year as an ordinal predictor disclosed large DIR reductions in 2001-2003 (odds ratio [OR] 0.11, CI95 0.06-0.19) and 2003-2004 (OR 0.22, CI95 0.14-0.34). Except for a moderate decrease in 2005-2006, no significant changes were detected afterwards. In both models, municipality-level DIRs correlated positively with previous-year DIRs and with the extent of municipal territory originally covered by montane dry forests. CONCLUSIONS/SIGNIFICANCE: Insecticide-spraying campaigns had very strong, long-lasting effects on DIRs in Cochabamba. However, post-intervention surveys consistently detected infestation in ∼3% of dwellings, underscoring the need for continuous surveillance; higher DIRs were recorded in the capital city and, more generally, in municipalities dominated by montane dry forest--an eco-region where wild Triatoma infestans are widespread. Traditional strategies combining insecticide spraying and longitudinal surveillance are thus confirmed as very effective means for area-wide Chagas disease vector control; they will be particularly beneficial in highly-endemic settings, but should also be implemented or maintained in other parts of Latin America where domestic infestation by triatomines is still commonplace.